Cryptosporidium infection induced the dropping of SCFAS and dysbiosis in intestinal microbiome of Tibetan pigs. (January 2023) - Chen, Xiushuang; Zhao, Xiaoxiao; Zhao, Chenxi; Ashfaq, Hassan; Fakhar-e-Alam Kulyar, Muhammad; Bhutta, Zeeshan Ahmad; Ali, Muhammad Muddassir; Mansoor, Muhammad Khalid; Li, Kun
Abstract: The infection of Cryptosporidium in pigs causes digestive system ailments, diarrhea and weight loss serving as an economic burden, especially in newborn animals. The bacterial fermentation products of short-chain fatty acids have important roles in immune function, microbiota regulation, osmotic balance and metabolism. However, till now little knowledge is available about the effect of Cryptosporidium infection on microbiota and SCFAs in plateau pigs. Hence, we performed this study to explore the response of microbiota and SCFAs in the natural infection of Cryptosporidium in Tibetan pigs. Cryptosporidium positive (infected, G) and negative samples (healthy, J) in our previous study were used for high throughputsequencing and Gas Chromatography-Mass Spectrometer analysis. Over 81 000 and 74 000 filtered sequences were detected in healthy and infected Tibetan pigs, respectively. Lower sample richness and evenness were observed in Cryptosporidium infection, as alpha diversity analysis found that chao1 ( p  < 0.05), faith_pd ( p  < 0.05), and observed_features in group G were significantly lower than pigs in group J. A total of 4 and 27 significant different phyla and genera were found between group G and J. The changed genera were Psychrobacter, Desemzia, Succiniclasticum, Treponema, Campylobacter, Atopobium, Olsenella, Pediococcus, Peptococcus, Sharpea, Desulfovibrio, Acinetobacter, Rhodococcus, Anaerostipes, Turicibacter, Lactobacillus, RFN20, Phascolarctobacterium, Roseburia, Megasphaera, Streptococcus, Blautia, Lachnospira, rc4_4, Gemmiger, Dorea, Oribacterium and Prevotella, which affected the microbiota functions with 360 abundance changed enzymes, and pathways in L1, L2 and L3 levels of KEGG. The concentration of acetic acid ( p  < 0.01), butyric acid ( p  < 0.05) and caproic acid ( p  < 0.01) were lower in group G. In conclusion, the present study herein uncovered that the host responses to Cryptosporidium infection in Tibetan pigs with 27 of significantly changed genera decreased SCFAs in pigs, which may provide insights in further developing novel therapy against this protozoan. Highlights: Cryptosporidium is an important pathogen causing serious diarrhea kid animals. Pigs are the important natural reservoir of Cryptosporidium spp. Cryptosporidium infection caused 27 significantly changed genera in Tibetan pigs. Cryptosporidium significantly decreased acetic acid, butyric acid and caproic acid in pigs.